ChipletEM: Physics-Based 2.5D and 3D Chiplet Heterogeneous Integration Electromigration Signoff Tool Using Coupled Stress and Thermal Simulation - Sun, Zeyu; Tong, Weijie; Ma, Xiaoning; Cao, He; Liu, Jianyun; Li, Zhiqiang; Xu, Qinzhi (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
A review of recent studies on up-to-date IC shows that electromigration (EM) has become one of the major challenges for 2.5D and 3D chiplet heterogeneous integration (CHI) systems. However, most existing researches on EM are focusing on 2D power delivery network without taking Through Silicon Via (TSV) and non-uniformly thermal distribution condition between dies into consideration. To address this problem, this article proposes a novel EM simulation tool ChipletEM for 2.5D and 3D CHI systems. A finite volume method (FVM) based electrical-thermal co-simulation model is employed to get initial temperature and current density inside TSV. And a finite difference time domain (FDTD) solver is used for hydrostatic stress simulation for both nucleation and postvoiding phases. Thermal migration (TM) effect is also considered in the solver. An analytical TSV thermal solver is employed for temperature distribution simulation and thermal dependent current simulation. The FDTD EM solver and TSV thermal solver are coupled together at each time step so that the interaction among EM stress, thermal stress, void growth, resistance change, IR drop and Joule heating effects can be simulated within a single simulation framework. Simulation results show that compared with Finite Element Method (FEM) tool, average error is 0.61% in nucleation phase and 2.4% in growth phase. And the error of proposed method is reduced from 22.22% to 5.24% compared with state of art atomic flux divergence (AFD) method.